Evaluation of the industry 4.0-based vocational high school development program - Suseno, Imam; Munali; Dewi, Shinta; Nurdin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The Directorate of Vocational High Schools (SMK) of the Ministry of Education, Culture, Research, and Technology has allocated government assistance funds for vocational high schools developed in accordance with Industry 4.0 for the 2021-2024 period. This program is designed to enhance the quality of graduates in line with the industrial world's needs, particularly in Special Economic Zones (SEZs) and Industrial Zones (IZs). Using the CIPP model to examine the impact of the Industry 4.0-based vocational high school development program, a proportional random sampling method was employed to select 63 schools as respondents. Data was collected through questionnaires, observations, and in-depth interview guides. Analysis of data from various sources concluded that there were positive impacts from the development of vocational secondary schools, including: digitization of the educational process; preparation for the adjustment of competencies required by in-dustry through the adjustment of the Industry 4.0-based curriculum; activation of the Learning Management System; optimization of the role of industry practitioners to im-prove the competencies of teachers and educators in schools; and renewal of practice room facilities and practice equipment. It is recommended that this program be continued and its distribution expanded outside SEZs and IZs.